Finding the molecular basis of complex genetic variation in humans and mice. - Mott, R (2006)
I survey the state of the art in complex trait analysis, including the use of new experimental and computational technologies and resources becoming available, and the challenges facing us. I also discuss how the prospects of rodent model systems compare with association mapping in humans.